Evaluasi Kepuasan Pengguna Terhadap Kualitas Layanan Sistem Pengembangan Daerah (Simbangda) Kabupaten Banyuasin Menggunakan Metode Electronic Government Quality - Ragil Tri Wahyudi; Gusmelia Testiana (UIR PRESS, 2022)
Sistem Pengembangan Daerah (Simbangda) Kabupaten Banyuasin is a public service as a forum for data and information from all Regional Government Organizations in the Banyuasin Regency environment to realize program Banyuasin Terbuka. A public service must be evaluated periodically to optimize the services provided. This study aims to evaluate user satisfaction with Simbangda's service quality using Electronic Government Quality (E-GovQual) method. The results showed that there were 5 variables in the level of satisfaction and 1 variable in the level of less satisfied. The variable ease of use averaged 2.80 in the satisfied category, trust with an average 2.75 in the satisfied category, functionality of the interaction environment with an average of 2.61 in the satisfied category, reliability with an average of 2.53 in the satisfied category, content and appearance with an average of 2.49 in the less satisfied category, and citizen support with an average of 2.99 in the satisfied category.